Analisis Keandalan Mesin Digester Menggunakan Metode Failure Mode And Effect Analysis Di Pabrik CPO PT Mas - Hegel Tottamor; Harwadi Harwadi; Indra Feriadi (Jurnal Inovasi Teknologi Terapan, 2026)
The digester machine is a critical unit in the palm oil processing industry, functioning to soften and mash palm fruit to enable optimal oil extraction. The reliability of this machine plays an important role in ensuring the continuity and efficiency of crude palm oil (CPO) production. This study aims to analyze the reliability of the digester machine at the CPO plant of PT MAS using the Failure Mode and Effect Analysis (FMEA) method. Research data were obtained through direct field observation, interviews with operators and maintenance technicians, and analysis of historical machine failure data from January to December 2024. Each failure mode was evaluated based on severity, occurrence, and detection parameters to determine the Risk Priority Number (RPN), which was used to establish maintenance priorities. The results indicate that the Expeller Arm and Short Arm components have the highest RPN values, identifying them as the most critical components with the highest risk of failure. Based on these findings, maintenance recommendations and corrective actions focused on critical components are proposed to improve the reliability of the digester machine, reduce downtime, and support efficient and continuous CPO production at PT MAS